Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Consider the differential equation $x''-(2t/1-t^2)x'+(2/1-t^2)x=0$ for $t$ in $(-1,1)$.

Show that $x(t)=t$ is a solution and find a second linearly independent solution $y(t)$.

So I get how to solve the equation and that $t$ is a solution, but how do I find another linearly independant solution?

Any help or suggestions much appreciated. I'm new here so sorry if I have done anything wrong!

share|improve this question
    
I think you have a typo there, because $x(t)=t$ is not a solution. –  gev Mar 20 '13 at 12:28
2  
@gev, I think it's meant to be read as $$x''-{2t\over1-t^2}x'+{2\over1-t^2}x=0$$, so $x=t$ is a solution. –  Gerry Myerson Mar 20 '13 at 12:33
add comment

3 Answers

up vote 1 down vote accepted

First, your equation I suppose in the shape of: $$x^{''}-{{2t}\over{1−t^2}}x^{'} +{{2}\over{1−t^2}}x=0$$ Your first solution is $x(t) = t$. So $x^{'}(t) = 1$ and $x^{''}(t) = 0$. Substituting into left hand part of the equation we get $0-{{2t}\over{1−t^2}}\cdot{1} +{{2}\over{1−t^2}}t = {{-2t+2t}\over{1-t^2}} = 0$ and this equals to right hand part of the equation, this means also {0}. So solution x(t) = t is one solution of the equation.
The second solution of the equation we assume in the shape of $x(t) = e^{kt}$, where k is value independent on t. So $x^{'}(t) = k{e^{kt}}$ and $x^{''}(t) = k^2{e^{kt}}$. Substituting into the equation we get: $k^2{e^{kt}}-{{2t}\over{1−t^2}}k{e^{kt}} +{{2}\over{1−t^2}}e^{kt}=0$. We need to identify {k} value. Because e^{kt} is not $0$ we can modify the form of the equation to $k^2-{{2t}\over{1−t^2}}k +{{2}\over{1−t^2}}=0$ and we now have for {k} the quadratic equation. Solving this quadratic equation we get $k_{1,2} = {{t\pm\sqrt{3t^2-2}}\over{1-t^2}}$.
So now we have two more terms which satisfy the equation: $$x(t)= {{t\pm\sqrt{3t^2-2}}\over{1-t^2}}$$(one with the $+$ sign in exponent a second with $-$ sign.
Whether this solution meets with everyone again by inserting:
${(t\pm\sqrt{3t^2-2})^2\over{{1-t^2}^2}}-{{2t}\over{1-t^2}}{{t\pm\sqrt{3t^2-2}}\over{1-t^2}}+{{2}\over{1-t^2}} = {{t^2\pm{2t\sqrt{3t^-2}}+3t^2-2-2t^2\mp{2t\sqrt{3t^-2}}+2-2t^2}\over{1-t^2}}={{0}\over{1-t^2}} = 0$. Is also equals to right hand part of equation. So both these solution also complies with the equation.
Including your solution we have three possible $x$: $$x(t) = t$$ $$x(t)= {{t+\sqrt{3t^2-2}}\over{1-t^2}}$$ $$x(t)= {{t-\sqrt{3t^2-2}}\over{1-t^2}}$$

share|improve this answer
    
amazing thank you SO much :) –  user67411 Mar 20 '13 at 14:44
add comment

There's a method for doing this, called reduction of order. I have linked to the Wikipedia article, which should get you started.

share|improve this answer
add comment

Hint: Assume the second solution is $ x_2(t)= u(t)x_1(t) = tu(t)$ and subs back in the ode to find $u(t)$. See here.

share|improve this answer
    
thats cool i thought this would be the way! Think i can solve the equation now! how to i find another linearly independant solution, is there a method for this? many thanks for your answer! –  user67411 Mar 20 '13 at 12:41
1  
@user67411: You are welcome. Note that, your ode is a linear second order ode which, by the theory, should have two linearly independent solutions. –  Mhenni Benghorbal Mar 20 '13 at 14:26
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.